INTEGRATION-INTERCONNECTION STUDY RATIONALITY AND SPIRITUALITY: RECONCILING THE RELATIONSHIP BETWEEN THE ABCDE TECHNIQUE IN REBT AND ISLAMIC TEACHINGS - Ummi Kalsum Aminsyah; Muhammad Arif Syailendra (AL-TAZKIAH, 2025)
This study is motivated by the need for a counselling approach that integrates psychological principles with Islamic spiritual values ​​to address individuals' emotional and cognitive challenges holistically. The ABCDE technique within Rational Emotive Behaviour Therapy (REBT) is considered relevant because it emphasises the role of beliefs in shaping emotional and behavioural responses, which aligns with Islamic teachings on self-reflection and inner awareness. The purpose of this study is to analyse the integration of the ABCDE technique of REBT with Islamic values ​​in the context of Islamic guidance and counselling. This research employs a qualitative approach, utilising a library research method to review relevant books, scholarly articles, and previous studies related to REBT and Islamic counselling. The findings suggest that the ABCDE technique enables individuals to recognise that emotional disturbances are not directly caused by external events, but rather by irrational beliefs about those events. When integrated with Islamic values ​​such as patience (sabr), trust in God (tawakkul), effort (ikhtiar), and acceptance of divine decree (qadar), individuals are better able to replace irrational beliefs with rational, constructive, and spiritually grounded perspectives. This integration supports emotional regulation, inner peace, and adaptive behaviour while strengthening spiritual awareness. The study concludes that integrating the ABCDE technique of REBT with Islamic values ​​contributes significantly to the development of holistic Islamic counselling practices by fostering balanced cognition, emotional stability, and spiritual resilience in facing life's challenges.